2018
DOI: 10.1007/s00394-018-1730-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hepatic inflammation and energy-sensing pathways in the rat liver by high-fructose diet and chronic stress

Abstract: High-fructose diet resulted in glucose intolerance, hepatic inflammation, decreased AMPK activity and reduced insulin sensitivity. Chronic stress alone did not exert such effects, but when applied together with high-fructose diet it could partially prevent fructose-induced inflammation, presumably due to increased hepatic glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
(87 reference statements)
1
8
2
1
Order By: Relevance
“…Our results are in agreement with those of previous studies showing that high fructose intake reduces nutrient-sensing signals [ 28 , 29 ]. Probiotic therapy has nearly no effect on renal nutrient-sensing signals at both mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with those of previous studies showing that high fructose intake reduces nutrient-sensing signals [ 28 , 29 ]. Probiotic therapy has nearly no effect on renal nutrient-sensing signals at both mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 94%
“…In our experiments, CS alone increased blood glucose concentrations, but had no significant effect on glucose tolerance [28] or on intrahepatic/intrarenal fat, fDNL, or VLDL-TG secretion. In contrast, the combined CS and HFr enhanced hypertriglyceridemia and fDNL-VLDL, while CS additionally potentiated the effects of HFr on increased IRTG-DNPalm content at the end of the feeding phase.…”
Section: Discussioncontrasting
confidence: 59%
“…Nevertheless, impaired glucose tolerance, which is a hallmark of hepatic and systemic insulin resistance, and increased inhibitory phosphorylation of IRS1 in hepatocyte, which is a marker of hepatic insulin resistance, were previously observed in HFr animals. [28] Noteworthy, in this former study, hyperinsulinemia and hypoglycemia were observed in HFr animals, which is most likely a result of overnight fasting. [29] In the current study, HFr increased the expression of fructose transporters and fructolysis enzymes in both liver and kidney, as well as renal expression of gluconeogenic genes, indicating that whatever portion of fructose escaped firstpass splanchnic uptake, it was sufficient to up-regulate fructose and glucose metabolism in the kidney.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations